2018
DOI: 10.12659/msm.909117
|View full text |Cite
|
Sign up to set email alerts
|

Association of Periodontitis with Rheumatoid Arthritis and the Effect of Non-Surgical Periodontal Treatment on Disease Activity in Patients with Rheumatoid Arthritis

Abstract: BackgroundThe association of periodontitis (PD) with the prevalence of rheumatoid arthritis (RA) remains controversial. Therefore, the aim of this study was to evaluate their correlation and investigate the effects of non-surgical periodontal treatment on RA.Material/MethodsA total of 64 patients were enrolled in this study and divided into 4 groups: 18 PD patients (PD+RA−), 18 RA patients (PD−RA+), 18 RA with PD patients (PD+RA+), and 10 healthy controls (PD−RA−). Periodontal and rheumatologic parameters were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(75 citation statements)
references
References 26 publications
(25 reference statements)
1
59
1
Order By: Relevance
“…In the RA-CP group, positive correlation was observed between periodontal parameters (GBI, PISA) and the rheumatology data ESR, while CAL and PPD were also positively correlated with 37,38 We observed in this study that females showed higher levels of LL-37 in both serum and saliva in the healthy group. This finding has also been reported in studies investigating the levels of LL-37 in plasma and urine samples of patients with urinary tract infection.…”
Section: F I G U R E 1 Correlation Between Salivary Ll-37 With (supporting
confidence: 53%
See 1 more Smart Citation
“…In the RA-CP group, positive correlation was observed between periodontal parameters (GBI, PISA) and the rheumatology data ESR, while CAL and PPD were also positively correlated with 37,38 We observed in this study that females showed higher levels of LL-37 in both serum and saliva in the healthy group. This finding has also been reported in studies investigating the levels of LL-37 in plasma and urine samples of patients with urinary tract infection.…”
Section: F I G U R E 1 Correlation Between Salivary Ll-37 With (supporting
confidence: 53%
“…presence of RA was not shown to worsen the severity of CP. 36,37 However, both studies mentioned that the presence of periodontitis was associated with RA disease progression. The subjects in Scher et al (2012) who showed that RA presented with worse CP conditions were newly diagnosed RA subjects without any treatment, 6 whereas the subjects in our study had been undergoing RA treatment for an average of 5-6 years.…”
Section: F I G U R E 1 Correlation Between Salivary Ll-37 With (mentioning
confidence: 99%
“…Evidence has suggested that citrullinated antigens in RA are mostly derived from NETs [98]. Patients with periodontitis may have RA and vice versa [99]. A recent publication has suggested that periodontal indices such as gingival index, probing pocket depth (PPD) and bleeding on probing (BOP) have positive relationships with RA.…”
Section: The Relationship Between Rheumatoid Arthritis Periodontitismentioning
confidence: 99%
“…35 Since then, three studies have been published, all of them reporting a significant improvement of RA parameters after periodontal therapy. [36][37][38] Although these results are promising, some authors have failed to observe this effect. In a case report of one RA patient undergoing periodontal treatment for 15 years, no beneficial effect was reported.…”
Section: Epidemiological Association Between Periodontitis and Ramentioning
confidence: 98%